TOWARDS THE EFFICIENCY AND EFFECTIVENESS OF REGIONAL GOVERNMENT BUDGETS, FOR THE PREPARATION AND DEVELOPMENT OF PUBLIC POLICIES (JURNAL ECONOMICA : Research of Economic And Economic Education, 2022)
Research focuses on the solve of problem efficiency and budgeting effectiveness in implementing economic development, especially in financing programs and activities through the West Sumatra Regional Budget. The data used are time series data issued by Indonesian Banks and the statistics center. Data analysis uses the mix methods as well as promethee, with six regional device organization analysis units. The research results that West Sumatra has not shown its independence and is still very dependent on assistance from the center to finance all obligations related to regional development and governance, so efforts to increase regional income are needed through intensification, extensification and improvement of services to the community as taxpayers. Expenditured allocation has not been balanced based on programs and activities of each development mission, the realization of indirect spending is higher than direct expenditure. The portion of local revenue is very small in its role in forming the West Sumatra Regional Budget with a constant growth trend over the past four years. The determinants of the inefficient use of the West Sumatra Regional Budget have been the realization of investment, economic growth, information systems and budgeting and the growth of stock capital, direct and indirect expenditure, providing public good, participation rates. The decision choices that are most appropriate compared to market allocation criteria and the majority rule. Macro economics, indirect spending, imports of capital goods and the level of bribery costs are criteria that are very sensitive to the choice of budgeting policies with the public allocation approach